Good strategy, bad strategy the difference and why it matters - Rumelt, Richard P. (New York Crown Business, 2011)
Developing and implementing a strategy is the central task of a leader, whether the CEO at a Fortune 100 company, an entrepreneur, a church pastor, the head of a school, or a government official. Richard Rumelt shows that there has been a growing and unfortunate tendency to equate Mom-and-apple-pie values, fluffy packages of buzzwords, motivational slogans, and financial goals with ?strategy.? He debunks these elements of ?bad strategy? and awakens an understanding of the power of a ?good strategy.?
Keywords: Strategic planning